Hubungan Antara Dukungan Sosial dengan Harga Diri pada Tunanetra Dewasa Mantan Awas di Kota Semarang - Vivi Savitri; Elis Hartati (Master of Nursing, Faculty of Medicine, Universitas Diponegoro, Indonesia, 2018)
Background: Visually impaired people is one of the most common disabilities in Indonesia. The number of visually impaired people in Semarang City based on the data of Central Bureau of statisic 2015 was 806 people. Sudden blindness can lead to depression, improper self-perception, decreased levels of motivation, and low self-esteem. The existence of Sosial support is one of the ways to help blind people spared from those impacts. Sosial support helps to deal the blind people with problems that relate to physically, psychologically, and sosially.Purpose: The purpose of this study is to analyze the relationship between sosial support and self-esteem in the former blind adult in Semarang.Method: The research uses non experiment quantity method with correlation method. The sampling technique use 50 correspondent of total sample. Data collection using a sosial support questionnaire and Coopersmith Self Esteem Inventory (CSEI). Results: The results showed that there was a correlation between sosial support and self-esteem of blind adults in Semarang with positive direction. Sosial support has an important role to increase self-esteem, the higher sosial support given the higher self-esteem of the blinds people get. The community is expected to be a provider of sosial support for fellow community members to increase self-esteem of the former visually impaired.